Valorization of the Phosphate Fertilizers Catalytic Activity in 1-(Benzothiazolylamino) Methyl-2-Naphthol Derivatives Synthesis - Omar Zimou; Badr Malek; Achraf Elhallaoui; Tourya Ghailane; Rachida Ghailane; Said Boukhris; Nouzha Habbadi; Amina Hassikou; Abdelaziz Souizi (Bulletin of Chemical Reaction Engineering & Catalysis, 2019)
The present work focused on developing a new protocol of the 1-(benzothiazolylamino) methyl-2-naphthol derivatives synthesis by condensation of three compounds, i.e. aromatic 2-naphthol, 2-aminobenzothiazole and aldehyde. Furthermore, this reaction was carried out in the presence of three heterogeneous phosphate catalysts: monoammonium phosphates (MAP), diammonium phosphate (DAP), and trisuperphosphate (TSP). Moreover, this method offered many advantages, such as: very high yields, shorter reaction times, and the catalysts, can be easily recovered and reused without any loss of their catalytic activities.